The Testament of Job and Its Function from the Perspective of Early Christianity - Naab, Ergo (Usuteaduslik Ajakiri, 2020)
The article examines the common motifs of the Testament of Job and New Testament literature. The research question is: what literary and theological motifs have encouraged the use of the work in a Christian context? The aim is to research the Testament of Job and its function from the perspective of early Christian eschatology, Christology, demonology and philanthropy.